AN ANALYTICAL STUDY OF FINANCIAL DISTRESS AND PROFITABILITY OF SBI AND ICICI BANK - Priyanka; Sheokand, Karamvir (International Journal of Research -GRANTHAALAYAH, 2017)
Financial distress is a situation in which a firm or company is not in position to pay its monetary obligation and debts and financial crisis start in the unit. It depicts the short term solvency of the banks. Profitability is the ability of business to earn profit. Profitability is the indication of good health of any business and it increase the value of a business. The main aims of this research paper are to investigate the level of financial distress in the SBI and ICICI bank and difference in the profitability of both banks ranging from 2013 to 2017. For measurement of the level of financial distress and profitability Altman Z-Score model and Independent t-test are used respectively. Result revealed that profitability of both banks was identical. Further study also revealed that both these banks were financially distressed.